MEDIA PUZZLE UNTUK KETERAMPILAN MENULIS SISWA KELAS X BAHASA 1 SMAN 1 GEDANGAN DALAM PEMBELAJARAN BAHASA JERMAN - LEMUNG, MARSELINA; IMAM SAMSUL, SUWARNO (LATERNE, 2018)
PUZZLE MEDIA FOR SKILLS WRITING STUDENT CLASS X SMAN 1 GEDANGAN IN GERMAN LEARNING Marselina Lemung German Language Education, Faculty of Language and Art, State University of Surabaya, Marselina_lemung@yahoo.co.id Drs. Suwarno Imam Samsul, M.pd German Language Education, Faculty of Language and Art, State University of Surabaya, Abstract Writing is an activity that people do to produce a writing. A good writing has its distinctly meaningful diantarannya is a one-unit, short and dense and meet the rules of language. Writing can be considered easy when one often practiced writing and can be considered difficult when a new person plunge or practice writing so do not know what to start from. This study uses simple sentences. A simple sentence is a sentence that has a subject element, predicate, and object. At the time of learning to write simple sentences many students have difficulty. The difficulty is caused by several factors namely lack of writing exercise, lack of vocabulary mastery, and ignorance of the meaning of the vocabulary. Therefore one of the learning media used to overcome this is using the media puzzle. The formulation of the problem in this research is "How the response of students of class X Language 1 SMAN 1 Gedangan on learning German language writing skills with the media puzzle" While the purpose of this study is "To Describe Response Students Class X Languages ??SMAN 1 Gedangan of learning skills writing with puzzle media ". This research is a qualitative research. Subjects in this study were students of grade X Language 1 SMA Negeri 1 Gedangan with a total of 33 students. The study was conducted three times face to face. Data collection techniques used are in the form of tests and questionnaire responses of students. The results of this study can increase student learning activities supported by the increase in the average student test results of the first test meeting 8.8, second meeting 93.93, third meeting 94.84 with good category. Questionnaire filling the response of learners in a very good category learning activity with an average of 5.78%. So it can be concluded that the puzzle media can be used in German writing skills. The success can be seen from the results of student tests and positive responses of students in the questionnaire.